Zero Waste Concept Of Strengthening And Food Safety Results Of Libuo Community Fisheries Residents Of Dungingi District Gorontalo City - Sri Subekti; Wahju Tjahjaningsih; Dwi Yuli Pujiastuti; Putri Desi Wulan Sari (OJS Universitas Muhammadiyah Gresik, 2020)
The potential of fishery resources in Gorontalo is quite abundant because of its strategic geographical position bordering Tomini bay. Gorontalo, especially in the Dungingi District, is one of the regions with promising potential fisheries resources where fishery application activities are not only focused on fish cultivation but also processing fishery products. However, people's understanding of fish processing that can only be obtained from their meat makes the community's income in the Libuo Village, Dungingi District Gorontalo City tend to be unstable. The Libuo community as fishery product processing actors need to be given an understanding of the potential and diversification of fishery products that can be produced from by-products that can be obtained from bones, scales, stomach contents, heads, and fish skins so that the application of zero waste can be implemented. Also, as an effort to increase public understanding related to the shelf life of fishery products which tends to be fast, the use of carrageenan as an alternative to edible coatings needs to be introduced to the community as a form of food safety of fishery products. Thus the benefits will be gained from increasing the added value of fisheries and a better level of food safety.